DebriefLive: A Pilot Study of a Virtual Faculty Development Tool for Debriefing. Issue 5 (October 2020) - Wong, Nelson L.; Peng, Cynthia; Park, Chan W.; Pérez, José; Vashi, Anita; Robinson, Jane; Okuda, Yasuharu
Abstract : Introduction: The quality of healthcare simulation learning relies heavily on effective debriefers. Traditional methods of faculty development in debriefing lack a structured approach to achieve expertise via graduated and reflective practice. Methods: The Simulation Learning, Education and Research Network (SimLEARN) developed DebriefLive, a virtual teaching environment, bringing together faculty and participant debriefers from across the Veterans Health Administration. Recorded simulation sessions were viewed followed by the opportunity for participant debriefers to debrief virtual learners. Participant debriefers were then provided structured and objective debriefings of the debriefings with the added opportunity for immediate practice. Program evaluation data for the pilot sessions were collected via electronic survey including a mix of Likert scale questions as well as short answer responses. Results: On a 7-point Likert scale, participant debriefers (n = 15) rated the content as effective (mean = 6.67, SD = 0.47) and appropriate to their level (mean = 6.47, SD = 0.47). The technology of video-based scenarios (mean = 6.6, SD = 0.61), followed by avatar-based debriefing sessions (mean = 6.6, SD = 0.8), was felt to be accurate and appropriate. All participants would agree or strongly agree with recommending this training program to colleagues. Conclusions: Simulation instructors and fellows across the spectrum of the Veterans Health Administration found the innovative computer-based faculty development program DebriefLive acceptable as well as effective in increasing self-efficacy in debriefing. DebriefLive is an innovative and potentially disruptive tool, combining best practices in simulation theory and virtual technologies, for the training and assessment of debriefers.